Association of hemorrhage at termination in caesarean scar pregnancy using the crossover sign of ultrasound image. Issue 8 (17th June 2020) - Wang, Yan; Tan, Guichun; Cheng, Xianghong; Xu, Yahui; Xu, Fuxia; Qu, Pengpeng
Abstract: Purpose: To analyze whether crossover sign (COS) can help predict the risk of bleeding during surgical evacuation in patients with caesarean scar pregnancy (CSP). Methods: This study retrospectively analyzed the clinical presentations, ultrasound images and treatment outcomes of patients with CSP. The relationship among the gestational sac, caesarean scar and the anterior uterine wall, defined as the COS, was analyzed to predict the risk of severe bleeding during surgical evacuation in these patients. All patients were categorized according to the relationship between the endometrial line and the superior–inferior diameter of the gestational sac into crossover sign‐1 and crossover sign‐2 groups. The Mann–Whitney U test was used to compare the data with non‐normal distribution, and logistic regression analysis was performed to identify the correlates of severe bleeding. Results: A total of 74 patients were included. In COS‐1 group ( n = 21), 16 (76.19%) patients suffered heavy bleeding(≥200 mL) during surgical evacuation, while COS‐2 group ( n = 53) had only 1(11.89%) patient complaint of heavy bleeding (≥200 mL) ( P < 0.01). Adverse surgical outcomes were more common in women with COS‐1. Logistic regression analysis showed that COS‐1 (OR, 7.93; 95% CI, 1.35–46.67) was independently associated with severe bleeding. Conclusion: COS can help predict who has a higher risk of severe hemorrhage in patients with CSP and guide the clinical treatment selection for optimal management of this condition.